2020
DOI: 10.1186/s12913-020-05660-1
|View full text |Cite
|
Sign up to set email alerts
|

Using routine health information data for research in low- and middle-income countries: a systematic review

Abstract: Background: Routine health information systems (RHISs) support resource allocation and management decisions at all levels of the health system, as well as strategy development and policy-making in many low-and middleincome countries (LMICs). Although RHIS data represent a rich source of information, such data are currently underused for research purposes, largely due to concerns over data quality. Given that substantial investments have been made in strengthening RHISs in LMICs in recent years, and that there … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 120 publications
(166 reference statements)
0
43
0
Order By: Relevance
“… 198 Although pragmatic use of routine health information is growing, it remains a small part of the overall LMIC health system evaluation literature. 199 We found only some evidence of significant harnessing of technology for trauma system evaluation. While health technology availability is inversely related to health need, 200 improving access to information technology is a widely recognised strategy to augment global health research capacity.…”
Section: Discussionmentioning
confidence: 72%
“… 198 Although pragmatic use of routine health information is growing, it remains a small part of the overall LMIC health system evaluation literature. 199 We found only some evidence of significant harnessing of technology for trauma system evaluation. While health technology availability is inversely related to health need, 200 improving access to information technology is a widely recognised strategy to augment global health research capacity.…”
Section: Discussionmentioning
confidence: 72%
“…Studies elsewhere have reported that data generated by health facilities are most often not sufficiently utilised to improve health care [24][25][26]. Generally, in Sub-Saharan Africa, health information utilisation at primary health care and the district is poor [22].…”
Section: Discussionmentioning
confidence: 99%
“…28 Data from routine health information systems (RHIS) are now widely available in LMICs and have been used to conduct similar analyses during other infectious disease outbreaks. 29 17 30 In this study, we use RHIS data to evaluate the impact of COVID-19 and its related response measures on the use of health services in Kinshasa during the first wave of the pandemic (March to September) to provide insights to inform the ongoing response and future infectious disease outbreaks.…”
Section: Bmj Global Healthmentioning
confidence: 99%